Electrochemical and Microbiological Characterization of Bioanode Communities Exhibiting Variable Levels of Startup Activity - Ortiz-Medina, Juan F.; Call, Douglas F. (Frontiers in Energy Research, 2019)
Microbial electrochemical technologies require the establishment of anode biofilms to generate electrical current. The factors driving bioanode formation and their variability during startup remain unclear, leading to a lack of effective strategies to initiate larger-scale systems. Accordingly, our objective was to characterize the electrochemical properties and microbial community structure of a large set of replicate bioanodes during their first cycle of current generation. To do this, we operated eight bioanode replicates at each of two fixed electrode potentials (−0.15 V and +0.15 V vs. standard hydrogen electrode) for one fed-batch cycle. We found that startup time decreased and maximum current generation increased at +0.15 V compared to −0.15 V, but at both potentials the bioanode replicates clustered into three distinct activity levels based on when they initiated current. Despite a large variation in current generation across the eight +0.15 V bioanodes, bioanode resistance and abundance of Geobacter species remained quite similar, differing by only 10% and 12%, respectively. At −0.15 V, current production strongly followed Geobacter species abundance and bioanode resistance, wherein the largest abundance of Geobacter was associated with the lowest charge transfer resistance. Our findings show that startup variability occurs at both applied potentials, but the underlying electrochemical and microbial factors driving variability are dependent on the applied potential.